Efektivitas Model Pembelajaran Kooperatif Tipe STAD terhadap Hasil Belajar Siswa - Dhyah Wardah Tsabita; Fika Oktaviani Zulkarnain; I Gusti Ayu Ratna Kumala Dewi Adi; Jenefer Delano Evaldus (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Primary research related to the implementation of the STAD type cooperative learning model on student learning outcomes has been widely conducted. These studies need to be identified, analyzed development, and drawn conclusions in general so that they can be used as suggestions for the progress of researchers and practitioners in the field of education. This study aims to see research trends by identifying and classifying all research results related to the application of the STAD model to student learning outcomes in Indonesia in 2016-2022. This study used the Systematic Literature Review (SLR) method. There were 20 related articles analyzed in this study. The results of this SLR show that research on the implementation of the STAD type cooperative learning model on student learning outcomes was most carried out in 2018 and 2019 and the most research subjects in elementary / MI students dominated by science and mathematics subjects. The most widely conducted research method is the classroom action method and in general the results show that the STAD model is able to have a positive impact or improve student learning outcomes better than other learning models. The results of this study can be a consideration for researchers in conducting research and for teachers in carrying out learning in the classroom.